Adsorptive material and application thereof in purification of wastewater containing thallium
Patent Information
- Application Number
- CN202410462285.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-17
AI Technical Summary
沉淀法(如中国专利CN115893772 B和CN109437386 B)现有技术主要为氧化沉淀和硫化沉淀,但药剂用量大、成本高,会产生大量的含铊废渣,且对低浓度的含铊废水处理深度不够
1)本发明利用低碳醇与海藻酸盐、羧甲基纤维素盐、柠檬酸盐、葡萄糖酸盐等进行改性,所得低碳醇改性有机盐作为吸附材料使用,对含铊废水中铊的吸附容量大、吸附速率快、去除效果好,经过吸附处理后含铊废水中的铊残留量低,具有广泛的应用前景。
Smart Images

Figure CN118105950B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an adsorption material, specifically to a low-carbon alcohol-modified organic salt and a composite adsorption material formed by its assembly with natural minerals, and also to the application of the adsorption material in the purification of thallium wastewater, belonging to the field of wastewater heavy metal treatment technology. Background Technology
[0002] Currently, thallium-containing wastewater treatment technologies mainly focus on precipitation, adsorption, ion exchange, and electrocoagulation. Precipitation methods (such as Chinese patents CN115893772 B and CN109437386 B) primarily involve oxidation and sulfide precipitation, but these methods require large amounts of reagents, are costly, generate significant amounts of thallium-containing waste residue, and are insufficient for treating low-concentration thallium-containing wastewater. Adsorption methods (such as Chinese patents CN104692561B and CN107227260B) utilize the high specific surface area or special functional groups of adsorbents to remove thallium, but existing adsorbents suffer from high costs, low adsorption capacity, complex regeneration processes, and difficulty in recycling. Ion exchange methods (such as Chinese patent CN108793492 B) are easily affected by organic matter and impurity ions in the wastewater and exhibit poor selectivity. Electrocoagulation (such as Chinese patent CN111186886 B) utilizes the sacrificial anode to generate highly active hydroxyl complexes and their hydroxides in situ, and removes thallium through adsorption, coagulation, and precipitation processes. It has high treatment efficiency, but the electrocoagulation process is not suitable for treating industrial wastewater with large fluctuations in thallium concentration, and it consumes a lot of electricity in the later stages, resulting in high costs. Summary of the Invention
[0003] In order to solve the technical problems existing in the existing methods and technologies, the first objective of the present invention is to provide an adsorbent material that has a large adsorption capacity, fast adsorption rate and good removal effect for thallium in thallium-containing wastewater. After adsorption treatment, the residual amount of thallium in the thallium-containing wastewater is low, and it has broad application prospects.
[0004] The second objective of this invention is to provide an adsorbent material for the purification of thallium-containing wastewater. This adsorbent material can rapidly and efficiently purify thallium in thallium-containing wastewater, and has low treatment costs, stable operation, no secondary pollution, simple regeneration process, and can be recycled, making it suitable for large-scale industrial applications.
[0005] To achieve the above-mentioned technical objectives, the present invention provides an adsorbent material comprising a low-carbon alcohol modified organic salt; the low-carbon alcohol modified organic salt is obtained by esterification reaction of low-carbon alcohol and organic salt; the organic salt includes at least one of alginate, carboxymethyl cellulose salt, citrate, and gluconate.
[0006] This invention uses low-carbon alcohols as modifiers to chemically modify organic compounds containing carboxylate groups, such as alginate, carboxymethyl cellulose salt, citrate, and gluconate. The low-carbon alcohols undergo esterification with the carboxylate groups of the organic compounds, converting some carboxylate groups into ester groups and causing chain transfer, while some hydrophilic groups are converted into hydrophobic groups. These hydrophobic groups act as templates, causing the low-carbon alcohol-modified organic salt molecules to aggregate into microspheres with a larger specific surface area in aqueous solution. The hydrophilic carboxyl and hydroxyl groups are fully exposed on the surface of the microspheres, thus promoting the complexation and coordination between the adsorbent and metal ions, enhancing adsorption performance and efficiency.
[0007] As a preferred embodiment, the mass ratio of the low-carbon alcohol to the organic salt is 1~3:1. If the proportion of low-carbon alcohol is too low, the modification effect on the organic salt is poor, the content of introduced hydrophobic groups is low, and the organic salt cannot aggregate into a microsphere structure with a high specific surface area, thus failing to effectively improve its adsorption performance and resulting in a low removal rate of thallium. If the proportion of low-carbon alcohol is too high, most of the carboxyl groups and other groups in the organic salt will be over-esterified, which will also reduce its adsorption performance for thallium.
[0008] As a preferred embodiment, the esterification reaction conditions are: a temperature of 60-90°C and a time of 8-10 hours. Controlling the esterification reaction under these preferred temperature and time conditions allows for appropriate esterification degree control, resulting in well-modified low-carbon alcohol organic salts.
[0009] As a preferred embodiment, the esterification reaction is performed under the following conditions: the lower alcohol is at least one selected from n-propanol, isopropanol, n-butanol, and isobutanol. Compared to methanol and ethanol, propanol and butanol have longer carbon chains, which are more conducive to acting as hydrophobic templates and are more likely to undergo nucleophilic reactions with carboxylate groups.
[0010] As a preferred embodiment, the adsorbent material comprises natural minerals and low-carbon alcohol-modified organic salts. The assembly and composite of natural minerals and low-carbon alcohols significantly enhances the adsorption capacity for thallium compared to a single low-carbon alcohol-modified organic salt. Based on the advantages of natural minerals, such as large specific surface area, porosity, and excellent physical adsorption properties, the composite assembly of natural minerals and low-carbon alcohol-modified organic salts allows the low-carbon alcohol-modified organic salts to be loaded onto the surface of the natural minerals, forming a novel composite adsorbent material with a large specific surface area, numerous reactive sites, and rich in functional groups such as hydroxyl and carboxyl groups. This achieves a synergistic effect of enhanced physical adsorption and complexation-coordination chemisorption of thallium ions. The composite process of natural minerals and low-carbon alcohol-modified organic salts can be completed simply by stirring and mixing the two in an aqueous solution.
[0011] As a preferred embodiment, the mass ratio of the natural mineral to the low-carbon alcohol-modified organic salt is 1:2 to 5. If the proportion of natural mineral is too low, its adsorption efficiency for thallium will be low, resulting in a relatively poor removal effect. If the proportion of natural mineral is too high, not only will the treatment cost increase, but the adsorption-regeneration cycle will also be short, which is detrimental to the sustainability of adsorption performance. Taking all factors into consideration, the mass ratio of the natural mineral to the low-carbon alcohol-modified organic salt is further preferably 1:3 to 5.
[0012] As a preferred embodiment, the natural mineral is at least one selected from montmorillonite, kaolinite, illite, sepiolite, halloysite, and attapulgite. When these natural minerals are combined with low-carbon alcohol-modified organic salts, the low-carbon alcohol-modified organic salts are fully loaded onto the surface, resulting in a significant increase in specific surface area (reaching up to 10³ m²). 2 / g, which is 1.5 to 3 times higher than that of single low-carbon alcohol modified organic salt and natural minerals, is more conducive to exposing more adsorption sites. At the same time, natural minerals themselves have certain adsorption activity. The synergistic adsorption effect of the two is obvious after combination. In addition, the composite adsorption material formed by natural minerals and low-carbon alcohol modified organic salts is simpler and more convenient to recycle, which is conducive to the recycling of adsorption materials.
[0013] The present invention also provides an application of an adsorbent material for the removal of thallium from thallium-containing wastewater.
[0014] As a preferred embodiment, the thallium concentration in the thallium-containing wastewater is 0.01~5000 mg / L.
[0015] As a preferred embodiment, the amount of the adsorbent added to the thallium-containing wastewater is 5.0% to 20.0% of the mass of thallium in the wastewater, and the stirring adsorption time is 20 to 30 minutes at room temperature.
[0016] As a preferred embodiment, the adsorbent material is used to adsorb thallium from thallium-containing wastewater, followed by filtration and separation. Thallium is then eluted with dilute acid to regenerate the adsorbent material. The dilute acid is either dilute nitric acid or dilute sulfuric acid, with a mass percentage concentration of 10-20%. The desorption principle is as follows: under acidic conditions, hydrogen ions in the solution can undergo a non-specific ion exchange reaction with thallium ions in the composite adsorbent, thus regenerating the composite adsorbent. The composite adsorbent material after dilute acid desorption can be recycled up to 5 times, with a thallium ion removal rate >90%.
[0017] Compared with the prior art, the beneficial technical effects of this invention are as follows: 1) This invention utilizes low-carbon alcohols modified with alginate, carboxymethyl cellulose salt, citrate, gluconate, etc., and the resulting low-carbon alcohol modified organic salts are used as adsorbent materials. They have a large adsorption capacity, fast adsorption rate, and good removal effect for thallium in thallium-containing wastewater. After adsorption treatment, the residual amount of thallium in the thallium-containing wastewater is low, which has broad application prospects.
[0018] 2) The low-carbon alcohol modified organic salt of the present invention is further combined with natural minerals to form a composite adsorbent material, which has a significantly increased specific surface area, making it more conducive to exposing more adsorption sites. At the same time, the natural minerals themselves have certain adsorption activity. The synergistic adsorption effect of the two after being combined is obvious, which greatly improves the purification effect of thallium-containing wastewater.
[0019] 3) The adsorption material of the present invention can be regenerated and recycled, and the regeneration process is simple, and the adsorption performance is sustainable.
[0020] 4) The thallium-containing wastewater purification method of the present invention has a simple process, low treatment cost, and high removal efficiency, avoiding the technical problems of high cost and complex regeneration process caused by the use of conventional adsorbents in the prior art. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the process flow for the preparation and application of the adsorption material of the present invention.
[0022] Figure 2 The images show the infrared spectra of sodium alginate adsorbent before and after modification in Example 1 of this invention.
[0023] Figure 3 The images shown are SEM and EDS images of the composite adsorbent material in Example 3 of this invention before it adsorbs thallium metal.
[0024] Figure 4 The images shown are SEM and EDS images of the composite adsorbent material after adsorbing thallium metal in Example 3 of this invention. Detailed Implementation
[0025] The following specific embodiments are intended to further illustrate the content of the present invention, rather than to limit the scope of protection of the claims of the present invention. Example 1
[0026] Take 10g of sodium alginate, then add 100mL of 20% isopropanol aqueous solution. React at 70℃ for 10 hours, then filter and wash. Place in a vacuum drying oven for 6 hours to obtain modified sodium alginate adsorbent. Fourier transform infrared spectroscopy was used to characterize sodium alginate and the modified sodium alginate. Figure 2As shown in the figure, under thorough stirring, 5 mg of modified sodium alginate adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 100 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.015 mg / L, with a thallium removal rate of 98.5%, indicating a good removal effect. Example 2
[0027] 10 g of sodium carboxymethyl cellulose was added to 80 mL of a 20% n-butanol aqueous solution. The reaction was carried out at 80 °C and stirred for 8 hours. The mixture was then filtered, washed, and placed in a vacuum drying oven for 6 hours to obtain the modified sodium carboxymethyl cellulose adsorbent. Under thorough stirring, 5 mg of the modified sodium carboxymethyl cellulose adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 100 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.010 mg / L, indicating a thallium removal rate of 99.0%, demonstrating good removal efficiency.
[0028] Comparative Example 1 Based on existing technology, 10g of sodium alginate was dissolved in 100mL of deionized water, followed by the addition of 20% calcium chloride. The mixture was stirred at room temperature for 10 hours, allowed to stand for 12 hours, filtered and washed, and then placed in a vacuum drying oven for 6 hours to obtain sodium alginate adsorbent. Under thorough stirring, 5mg of sodium alginate adsorbent was added to 500mL of thallium-containing wastewater with a thallium concentration of 100mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.083mg / L, with a thallium removal rate of 91.7%, indicating a poor removal effect.
[0029] Comparative Example 2 Under thorough stirring, 5 mg of unmodified sodium carboxymethyl cellulose adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 100 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.088 mg / L, with a thallium removal rate of 91.2%, which is considered poor.
[0030] Example 3
[0031] Take 10g of modified sodium alginate from Example 1 and 30g of natural kaolinite mineral (with a specific surface area of 55m² as measured by N2-BET). 2(g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain a novel composite adsorbent (specific surface area measured by N2-BET was 104 m²). 2 / g). Under thorough stirring, 50 mg of the composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. The novel composite adsorbent before and after thallium ion adsorption was tested using scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS), such as... Figure 3 and 4 As shown in the figure. After treatment, the thallium content in the wastewater after adsorption was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0005 mg / L, with a thallium removal rate of 99.99%, indicating an excellent removal effect.
[0032] Comparative Example 3 Take 10g of unmodified sodium alginate and 30g of natural kaolinite mineral (with a specific surface area of 46 m² measured by N2-BET). 2 (g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain the composite adsorbent (specific surface area measured by N2-BET was 62 m²). 2 / g). Under thorough stirring, 50 mg of composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 1.572 mg / L, with a thallium removal rate of 99.71%, which is not thorough. Example 4
[0033] Take 10g of modified sodium alginate from Example 1 and 30g of natural sepiolite mineral (with a specific surface area of 62m² measured by N2-BET). 2 / g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain a novel composite adsorbent (specific surface area of 127 m² measured by N₂-BET). 2 / g). Under thorough stirring, 50 mg of composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0010 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency.
[0034] Comparative Example 4 Take 10g of unmodified sodium alginate and 30g of natural sepiolite mineral (with a specific surface area of 53 m² measured by N2-BET). 2 / g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain a novel composite adsorbent (specific surface area of 92 m² measured by N₂-BET). 2 / g). Under thorough stirring, 500 mg of composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 1.012 mg / L, with a thallium removal rate of 98.98%, which is not thorough. Example 5
[0035] Take 10g of modified sodium carboxymethyl cellulose from Example 2 and 30g of natural montmorillonite mineral (with a specific surface area of 58m² as measured by N2-BET). 2 / g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain a novel composite adsorbent (specific surface area measured by N2-BET was 146 m²). 2 / g). Under thorough stirring, 50 mg of composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0010 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency. Example 6
[0036] Take 10g of modified sodium carboxymethyl cellulose from Example 2 and 30g of natural attapulgite mineral (with a specific surface area of 63m² measured by N2-BET). 2 / g), then added together to 400 mL of deionized water, stirred thoroughly for 3 hours, filtered, and vacuum dried for 5 hours to obtain a novel composite adsorbent (specific surface area measured by N2-BET was 139 m²). 2 / g). Under thorough stirring, 50 mg of composite adsorbent was added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, and the thallium was removed from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0008 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency. Example 7
[0037] The composite adsorbent obtained from the adsorption in Example 3 was desorbed using 10% dilute nitric acid, rinsed three times with deionized water, and then added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0012 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency. Example 8
[0038] The composite adsorbent from Example 7 was desorbed again using 10% dilute nitric acid, rinsed three times with deionized water, and then added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0014 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency. Example 9
[0039] The composite adsorbent from Example 8 was desorbed for the third time using 10% dilute nitric acid, rinsed three times with deionized water, and then added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0019 mg / L, with a thallium removal rate of 99.99%, indicating excellent removal efficiency. Example 10
[0040] The composite adsorbent from Example 9 was desorbed for the fourth time using 10% dilute nitric acid, rinsed three times with deionized water, and then added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.0082 mg / L, with a thallium removal rate of 99.99%, indicating a good removal effect. Example 11
[0041] The composite adsorbent from Example 10 was desorbed for the fifth time using 10% dilute nitric acid, rinsed three times with deionized water, and then added to 500 mL of thallium-containing wastewater with a thallium concentration of 1000.0 mg / L. The mixture was stirred at room temperature for 20 minutes, followed by solid-liquid separation, removing thallium from the wastewater. After treatment, the thallium concentration in the wastewater was determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 0.067 mg / L, with a thallium removal rate of 99.98%, indicating a good removal effect.
Claims
1. An adsorbent material, characterized in that: It contains natural minerals and low-carbon alcohol modified organic salts; after the natural minerals are combined with the low-carbon alcohol modified organic salts, the low-carbon alcohol modified organic salts are fully loaded on the surface of the natural minerals. The low-carbon alcohol modified organic salt is obtained by esterification reaction of low-carbon alcohol and organic salt; The organic salt includes at least one of alginate, carboxymethyl cellulose salt, citrate, and gluconate; The low-carbon alcohol is at least one of n-propanol, isopropanol, n-butanol, and isobutanol; the natural mineral is at least one of montmorillonite, kaolinite, illite, sepiolite, halloysite, and attapulgite.
2. The adsorbent material according to claim 1, characterized in that: The mass ratio of the low-carbon alcohol to the organic salt is 1~3:
1.
3. An adsorbent material according to claim 1 or 2, characterized in that: The esterification reaction conditions are: temperature 60~90℃, time 8~10 hours.
4. The application of the adsorbent material according to any one of claims 1 to 3, characterized in that: Used for thallium removal from thallium-containing wastewater.
5. The application of the adsorbent material according to claim 4, characterized in that: The adsorbent material is used to adsorb thallium in thallium-containing wastewater, then filtered and separated, and thallium is eluted with dilute acid to complete the regeneration of the adsorbent material.
Citation Information
Patent Citations
A method for deep treatment of thallium-containing wastewater
CN104692561B
A biosorbent for adsorbing thallium ions, its preparation method and application
CN107227260B
A method for deep thallium removal from industrial wastewater
CN108793492B
A method for removing thallium from wastewater
CN109437386B
A method for removing and recovering thallium from industrial wastewater
CN111186886B